ANALISIS JARINGAN SOSIAL PADA ARTIKEL TERKAIT USAHA KECIL DAN MENENGAH DI INDONESIA - Yaman, Aris (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2017)
The amount of contribution of SMEs to be balanced by a reception with great competitiveness. Innovation is a way of improving competitiveness. Contributions researchers and academics can be seen from innovations made through scientific publications. The government should provide incentives to researchers who focus on the development of Indonesian SMEs to improve the nation's competitiveness. Due to budget constraints, the government needs to streamline and streamline the budget incentives for research related to SMEs Indonesia. In addition to seeing the productivity aspects of scientific publications, is necessary to study the centrality of a writer/agency relationships in social network analysis co-authorship. In terms of productivity Institut Teknologi Bandung (ITB) become the most productive agencies to publish articles related to SMEs Indonesia. Judging from the social networking aspect, the University of Indonesia became the central figure in scientific publications related to SMEs Indonesia. Thus, social network analysis co-authorship relations can be used as another aspect in determining the actor/isntansi influential scientific publications related to SMEs in Indonesia.